Electric circuits - Nilsson, James W.; Riedel, Susan A. (Pearson Prentice Hall, 2008)
Electric Circuits, Eighth Edition features a new design,a four-color format, and 80% of chapter problems have been updated. In the midst of these changes, the book retains the goals that have made it a best-seller: 1) To build an understanding of concepts and ideas explicitly in terms of previous learning; 2) To emphasize the relationship between conceptual understanding and problem solving approaches; 3) To provide readers with a strong foundation of engineering practices.